Edaravone dexborneol protected neurological function by targeting NRF2/ARE and NF-κB/AIM2 pathways in cerebral ischemia/reperfusion injury - Zhang, Hui; Zhu, Can; Zhou, Xingyu; Wang, Laifa; Deng, Ling; He, Binsheng; Li, Jianming (Frontiers in Pharmacology, 2025)
BackgroundEdaravone dexborneol (Eda-Dex), a promising neuroprotectant composed of edaravone and (+)-borneol, has been clinically applied in stroke treatment. However, the mechanism of action of Eda-Dex remains unclear.MethodsA rat model of cerebral ischemia/reperfusion injury (CIRI) was created through middle cerebral artery occlusion. Neurological scoring, TTC staining, and laser speckle imaging were used to assess neurological deficits, infarct size and cerebral blood flow (CBF). Behavioral tests, including the open field test, the elevated plus maze, and the novel object recognition test, were conducted to assess animal behavior. Western blotting and ELISA were employed to assess levels of expression of components of the NRF2/ARE and NF-κB/AIM2 pathways and of specific cytokines. The levels of oxidative stress markers were analyzed via commercially available kits. HE staining, Nissl staining, and immunohistochemistry were used to assess pathological alterations in the brain.ResultsEda-Dex dramatically reduced the neurological deficit score and cerebral infarct size, increased CBF, and attenuated anxiety-like behavior and improved cognitive function in CIRI rats. Eda-Dex significantly reduced oxidative stress and relieved inflammatory response and it significantly upregulated NRF2, NQO1, HO-1, and SLC7A11 and significantly downregulated NF-κB, AIM2, ASC and caspase 1 in the infarcted brain. Moreover, Eda-Dex clearly reduced pathological damage, rescued neurons, and reduced the activation of microglia and astrocytes.ConclusionsThe results of this study confirm that Eda-Dex exerts neuroprotective effects by synergistically inhibiting oxidative stress and inflammation via the NRF2/ARE and NF-κB/AIM2 pathways in CIRI rats.